Efektifitas Promosi Kesehatan melalui Focus Group Discussion (FGD) terhadap KAP Remaja Putri Terkait Anemia Defisiensi Besi dalam Upaya Preventif Penurunan Stunting - Nurbaiti, Lina; Buanayuda, Gede Wira; Faradina Z, Fitriannisa (Bima Nursing Journal, 2025)
Teenage girls who are anemic are at risk of developing anemia during pregnancy, which negatively affects fetal growth and development and can lead to complications during pregnancy and childbirth, including maternal and infant death. Anemia is also a major contributor to stunting in newborns of anemic mothers. Therefore, efforts to prevent and treat anemia in women of reproductive age are very important. Health promotion activities through FGDs to improve the cognitive (knowledge), affective (attitude) and psychomotor (behavior) of adolescent girls regarding the prevention and control of anemia, especially regarding the importance of TTD consumption, are expected to reduce the prevalence of anemia in adolescent girls and ultimately reduce stunting rates. Methods: Forty-eight teenage girls selected through multistage random sampling from several junior high schools in Mataram that were participating in the blood additive tablet (TTD) program were intervened with health promotion activities using the focus group discussion (FGD) method, and knowledge, attitudes, and behaviors were measured before and after the intervention. Activities were conducted during June-September 2023. Data were analyzed using the Wilcoxon test. Results: There was an increase in cognitive affective and psychomotor skills of the respondents after FGD activities. At the beginning of the activity, the average cognitive score (knowledge) of adolescent girls about anemia was still low, which was around 58.5 shown by 65.3% of respondents. The average cognitive score (knowledge) increased to 87.5 for most (87.6%) of the respondents. The majority of the respondents had a positive attitude (affective) (97.3%) towards anemia and its prevention before the FGD activity, after the FGD activity the positive attitude of the respondents was 100%. Most of the respondents also did not apply good action (psychomotor) in preventing anemia (86.7%) and only 13.3% applied good action before conducting FGDs. After the FGD, 76.5% of the respondents, after the FGD activity, the positive attitude of the respondents was 100%. Most of the respondents also had not taken good (psychomotor) measures to prevent anemia (86.7%) and only 13.3% had taken good measures before the FGD. After the FGD activities, 76.5% of the respondents experienced an improvement in their anemia prevention efforts. Conclusion: There is a significant increase in cognitive affective and psychomotor in teenage girls related to iron deficiency anemia in preventive efforts to reduce stunting.